THE REVOLUTION OF ISLAMIC EDUCATION THOUGHT IN THE ERA OF SOCIETY 5.0: CORRECTIONS AND ANALYSIS OF STUDIES IN ISLAMIC HIGHER EDUCATIONINSTITUTIONS IN SOUTH KALIMANTAN - Gamar Al Haddar; Haerudin; Agus Riyanto; Abdul Wahab Syakhrani; Aslan Aslan (International Journal of Teaching and Learning, 2023)
The revolution of Islamic education thought in the era of Society 5.0 was characterized by a series of corrections and in-depth analysis of studies conducted in Islamic higher education institutions in South Kalimantan. During this transformative period, scholars and educators within these institutions began to reevaluate and refine their educational methodologies. They identified deficiencies in traditional teaching approaches and employed innovative strategies to adapt to the evolving needs of society. Technological advancements were pivotal in this revolution, as online platforms, interactive learning tools, and digital resources were integrated into the curriculum. This shift expanded access to education and enhanced the overall quality of teaching and learning. Moreover, faculty members conducted extensive research and critically assessed the existing educational paradigms. The outcomes of these studies guided the development of curricula that were more responsive to the contemporary challenges faced by students. The corrections and analyses fostered a dynamic and student-centric educational environment, ultimately preparing graduates to thrive in the complex, technology-driven landscape of Society 5.0.